Cultural Method Considerations for Integrated Weed Management in Agronomic Crops - Prasanna Kharel; Pratap Devkota; Gregory MacDonald (EDIS)
This article provides growers with information on various cultural methods to increase weed control in their fields, reduce herbicide inputs, and contribute to integrated weed management. Written by Prasanna Kharel, Pratap Devkota, and Greg MacDonald, and published by the UF/IFAS Agronomy Department, May 2021.